What Regions Do Rather than Make: A Proposed Set of Knowledge-based Occupation Clusters. - Feser, Edward J. (Urban Studies (Routledge), 2003)
With the expansion of knowledge-intensive industries in the US, along with intensifying focus on workforce development policy as an economic development strategy, occupations are increasingly being used as basic units of analysis in applied studies of urban and regional economies. An heretofore underappreciated component of occupation-based regional analysis is the need to understand relationships, similarities and dissimilarities among occupations themselves, so that they may be aggregated or grouped in theoretically and empirically meaningful ways. This paper lays out a conceptual framework and empirical approach to identifying knowledge-based occupation clusters, or groups of occupations that share the same broad knowledge characteristics. Following an application of the clusters to a comparison of labour pools in a selected 38 metropolitan economies, the paper discusses the clusters' general value for regional economic analysis, especially their utility as an intermediate step in applied industry cluster analyses where necessary regional occupation data are limited.